Non-Deterministic Planning With Conditional Effects - Muise, Christian; McIlraith, Sheila; Belle, Vaishak (Proceedings of the International Conference on Automated Planning and Scheduling, 2014)
Recent advances in fully observable non-deterministic (FOND) planning have enabled new techniques for various applications, such as behaviour composition, among others. One key limitation of modern FOND planners is their lack of native support for conditional effects. In this paper we describe an extension to PRP, the current state of the art in FOND planning, that supports the generation of policies for domains with conditional effects and non-determinism. We present core modifications to the PRP planner for this enhanced functionality without sacrificing soundness and completeness. Additionally, we demonstrate the planner’s capabilities on a variety of benchmarks that include actions with both conditional effects and non-deterministic outcomes. The resulting planner opens the door to models of greater expressivity, and does so without affecting PRP’s efficiency.